Efektifitas Jus Seledri Terhadap Penurunan Tekanan Darah Pada Lansia Penderita Hipertensi Di Wilayah Kerja Puskesmas Simalingkar - Lasria Simamora; Srilina Br.Pinem; Nurhamida Fithri (Journal of Health (JoH), 2021)
Hypertension is an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg on two measurements with an interval of five minutes in a well-rested state. Hypertension control can be done with a pharmacological approach and non-pharmacological.One of the non-pharmacological treatments is to use celery. Celery contains apigenin, flavonoids, vitamin C, apiin, calcium, and magnesium to prevent constriction of blood vessels and help lower high blood pressure. This study aims to analyze the effectiveness of celery juice on reducing blood pressure in elderly people with hypertension in the Simalingkar Health Center. This study used a pre post experimental design. The number of respondents in the work area of ​​the Simalingkar Community Health Center was 10 respondents with a significance level of <0.05. The results showed that the systole p value was 0.000 (<0.05) and the diastole was 0.000 (<0.05), which means that celery juice had a significant effect on reducing blood pressure. The mean reduction in systolic blood pressure was 30 mmHg and distolic 14 mmHg. The results of statistical tests obtained a p-value of 0.000 (<0.5), it was concluded that celery juice was effective in reducing blood pressure.